Improving the Nutritional Quality (Protein, Fat, Ash and Water Content) of Water Spinach (Ipomoea Reptans Poir) Through Aquaponics and Hydroponics - Dewi Suryani Oktavia B; Sata Yoshida Srie Rahayu; Sa'i Hendri Yana (SEAMEO BIOTROP, 2026)
Soilless cultivation such as hydroponics and aquaponics is now a popular alternative for modern agriculture. Water spinach (Ipomoea Reptans Poir) is widely cultivated, but the influence of cultivation techniques on its proximate values ​​remains minimal. This study aims to analyze and compare the water, protein, fat, ash, and carbohydrate content of water spinach from hydroponic, aquaponic, and conventional cultivation. The methods cover the cultivation process up to harvest, as well as proximate analysis (SNI 01-2891-1992). The results show that cultivation techniques influence nutrient content. Hydroponic water spinach has the highest protein, fat, and ash content; aquaponic water spinach has the highest water content; and conventional water spinach has the highest carbohydrate content. These differences demonstrate the importance of selecting cultivation methods according to nutritional needs and the potential for improving nutritional quality through hydroponics and aquaponics.